Descriptive Morphology, Morphometry, Community Structure and Spatial Distribution of Helminth Parasites in the Malayan Box Turtle, Cuora Amboinensis (Chelonia: Bataguridae) From Peninsular Malaysia - Sharma, Reuben Sunil Kumar (2001)
Thirty-six wild-caught Cuora amhoinensis from Peninsular Malaysia, comprising adults and juveniles of both sexes, were examined for helminth endoparasites. A total of 11 species (5 nematodes and 6 trematodes) were recovered from various organs, namely, Selpinema octorugatus (small intestine), Falcaustra duyagi (large intestine), Falcaustra sp. 1 (large intestine), Oxyurid larvae sp. 1 (liver), Oxyurid larvae sp. 2 (large intestine), Atractidae sp. (large intestine), Parorientodiscus magnus (large intestine), Digenea sp. 1 (liver), Digenea sp. 2 (large intestine), Polystomoides malayi (urinary bladder), and Polystomoides asiaticus (oral cavity). Seven of these helminths were not previously recorded in C. amboinensis, while 4 species, namely Falcaustra sp. 1, Digenea spp . 1 and 2., and the Atractidae sp. may be new species and geographical records, and require further taxonomic workout. The morphology and morphometry of 4 helminth species, namely, S. octorugatus, F. duyagi, P. magnus and P. malayi were studied in detail. A rigorous redescription of S. octorugatus was done with the aid of SEM and Pepsin-HCL digestion. New information was obtained including the number and arrangement of the buccal ridges, the absence of the lateral papillae, the addition of a fifth post anal papillae and the complex structure of the spicule tip. This study also demonstrated the usefulness of the relative positions of the caudal papillae and derived ratios, in the characterisation of the genus Selpinema. The helminth community structure of C. amboinensis in relation to age, gender and lifestage categories was investigated for the first time. This chelonian had a rich assemblage of helminths (observed richness = 11; expected richness, Cha02 = 9.17), with high diversity (Shannon's index = 0.78) and low evenness (0.36). This supports previous claims that C. amboinensis is vagile in food habits and habitat selection. Two helminths, namely S. octorugatus and F duyagi exhibited high intensity and prevalence, and were designated as core and dominant species, while Falcaustra sp. 1 and Oxyurid sp. 1 were regarded as unsuccessful pioneers. The helminth community structure between the various hosts age, gender and life stage categories were different, and may be attributed to disparate feeding habits and habitat utilisation. Results on the spatial distribution of the helminths found in the alimentary canal of C. amboinensis indicate that the worms are site specific, with a relatively narrow niche width. Further, interspecific competition may not be a prominent factor in determining the habitat restriction of helminths in this turtle host. Significant and positive correlation (Spearman' s rank coefficient = 0.45, P<0.05) was found between the intensity and prevalence of S. octorugatus and the packing density of the mucosal folds in the cranial duodenum. These helminths may actively select this niche, as the close proximity of the mucosal folds arranged in a complex labyrinth provide structural support and added traction, which function to stabilise the attachment interface. The large intestinal nematode (F duyagi), on the contrary, appeared to select its habitat based on physiological rather than morphological cues. It is likely that this luminal feeder is attracted to the prolonged retention of food material in the large intestine, and the presence of particulate digesta and abundant micro-organisms.